37 Dynamic Changes in T-Lymphocyte Counts Following Primary Percutaneous Coronary Intervention Predict Infarct Size and Microvascular Obstruction. (31st May 2014) - Boag, Stephen; Schmeleva, Evgeniya; Das, Rajiv; Egred, Mohaned; Zaman, Azfar; Bagnall, Alan; Andrew Owens, W; Keavney, Bernard; Ahmed, Javed; Spyridopoulos, Ioakim
Abstract : Introduction: Although primary percutaneous coronary intervention (PPCI) has revolutionised treatment of myocardial infarction, ischaemia-reperfusion (I/R) injury remains an important complication. Microvascular obstruction (MVO) is one component of I/R injury, and is of prognostic significance independent of infarct size. We have previously demonstrated changes in T-lymphocyte counts in the blood following PPCI for STEMI. The goal of this study was to investigate a potential role for T-cells in myocardial I/R injury. Methods: We analysed blood from 38 STEMI patients undergoing PPCI. Samples were taken at the start of the procedure and at 15, 30, 90 min, and 24 h post reperfusion. In 6 patients with anterior infarcts, coronary sinus (CS) blood was also obtained at 30–60 min, along with simultaneous aortic blood. Differential leucocyte counts, including detailed lymphocyte subsets, were obtained using 8 colour flow cytometry. Cardiac MRI was performed at 1–7 days, and infarct size, MVO (on late gadolinium enhancement images), area at risk (on T2-weighted STIR images) and salvage index quantified. Results: Different leucocyte populations displayed characteristic dynamic changes in their cell counts following reperfusion. T-lymphocytes dropped between 0 and 90 min by a mean of 33% (0min mean 1520 cells/μl, 90min mean 918/μl), followed by recovery until 24 h (mean 1630/μl). Changes in CD8 T-cells were greater than CD4 T-cells (mean 0–90min drop and 90min-24hr increase: 45% and 128% respectively for CD8s, 24% and 75% for CD4s). In both CD4 and CD8 T-cells, the more highly differentiated CCR7- subpopulations (effector memory and TEMRA cells) displayed greater changes than CCR7+ cells (naive and central memory) e.g. 0–90min drop for CD8 naive: 19%, CD8 TEMRA: 53%. The increase in total T-cell and CD4 T-cell count between 90 min and 24hrs correlated in infarct size (total T-cells: r = 0.482, p < 0.01, CD4 T-cells: r = 0.521, p < 0.01) and negatively with salvage index (total T-cells: r = -0.481, p = 0.03, CD4 T-cells: r = -0.495, p = 0.02). MVO, however, showed a very strong relationship with the drop between 15 and 30 min post reperfusion (total T cells: r = -0.711, p < 0.001, CD4: r = -0.711, p < 0.001, CD8: r = -0.664, p < 0.001). Simultaneous CS and aortic sampling in a subset of anterior STEMIs (n = 6) demonstrated a significant drop in total T-cells (mean drop 3.5%) and CD4 T-cells (3.3%) across the coronary circulation. Conclusions: Acute dynamics in T-cell counts following PPCI for STEMI predict infarct size, salvage index and MVO. In particular, the strong correlation between MVO and early changes following reperfusion suggest a possible mechanistic link. The presence of a trans-coronary gradient in total T-cell and CD4 T-cell counts suggests that some of these cells may be sequestered into the reperfused myocardium, where they contribute to I/R injury. This provides the first evidence in humans of a role for T-cells in myocardial I/R injury.